Deletion of C2orf34, PREPL and SLC3A1 causes atypical hypotonia–cystinuria syndrome. Issue 5 (30th January 2008) - Chabrol, B; Martens, K; Meulemans, S; Cano, A; Jaeken, J; Matthijs, G; Creemers, J W M
Abstract : Background: Hypotonia–cystinuria syndrome (HCS) and 2p21 deletion syndrome are two recessive contiguous gene deletion syndromes associated with cystinuria type I. The deletions differ in size and the number of genes involved. In HCS patients, only SLC3A1 and PREPL are disrupted. In the 2p21 deletion syndrome, two additional genes ( C2orf34 and PPM1B ) are lost. Objective: Clinical and molecular analysis of two siblings who presented with an atypical HCS phenotype. Methods: Molecular analysis of the SLC3A1/PREPL locus was performed in the patients using quantitative polymerase chain reaction (PCR) methods. Results: HCS in both siblings was confirmed with the deletion screen of the SLC3A1/PREPL locus. Fine mapping of the breakpoint revealed a deletion of 77.4 kb, including three genes: SLC3A1, PREPL and C2orf34 . Features not present in classical HCS were a mild/moderate mental retardation and a respiratory chain complex IV deficiency documented in patient 2. Conclusions: We report the first patients with a deletion of SLC3A1, PREPL and C2orf34 . They present with a phenotype intermediate between HCS and 2p21 deletion syndrome. These patients facilitate the elucidation of the contribution of each gene to the phenotype in the different 2p21 deletion syndromes.